2020
DOI: 10.1167/iovs.61.13.13
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Cytosolic Calpain, Not Caspase, Is Underlying Mechanism for Hypoxic RGC Damage in Human Retinal Explants

Abstract: Activation of proteolytic enzymes, calpains and caspases, have been observed in many models of retinal disease. We previously demonstrated calpain activation in monkey retinal explants cultured under hypoxia. However, cellular responses are often speciesspecific. The purpose of the present study was to determine whether calpains or caspase-3 was involved in retinal ganglion cell (RGC) damage caused by hypoxia/reoxygenation in human retinal explants. The explant model was improved by use of an oxygen-controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 53 publications
2
3
0
Order By: Relevance
“…Moreover, PD150606, a nonpeptide, cell-permeable selective calpain inhibitor, inhibits calpains by binding to the calcium-binding site of the enzyme. Numerous studies have proved that calpain is a promising therapeutic target in many diseases, such as I/R injury (Zu et al 2020), cardiomyocytes hypertrophy (Li et al 2020), and renal diseases (Kobayashi-Otsugu et al 2020). Consist with other researches, our results demonstrated that the inhibition of calpain, Fig.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Moreover, PD150606, a nonpeptide, cell-permeable selective calpain inhibitor, inhibits calpains by binding to the calcium-binding site of the enzyme. Numerous studies have proved that calpain is a promising therapeutic target in many diseases, such as I/R injury (Zu et al 2020), cardiomyocytes hypertrophy (Li et al 2020), and renal diseases (Kobayashi-Otsugu et al 2020). Consist with other researches, our results demonstrated that the inhibition of calpain, Fig.…”
Section: Discussionsupporting
confidence: 76%
“…Moreover, PD150606, a nonpeptide, cell-permeable selective calpain inhibitor, inhibits calpains by binding to the calcium-binding site of the enzyme. Numerous studies have proved that calpain is a promising therapeutic target in many diseases, such as I/R injury (Zu et al 2020 ), cardiomyocytes hypertrophy (Li et al 2020 ), and renal diseases (Kobayashi-Otsugu et al 2020 ). Consist with other researches, our results demonstrated that the inhibition of calpain, both by calpastatin overexpression and PD150606 intervention, attenuated myocardial injury, alleviated cardiac inflammation, improved mitochondrial function, and reduced apoptosis in VMC, implying calpain activation promoted the severity of CVB3-induced myocarditis.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of glutamine synthase has also been reported to diminish during aging owing to oxidation (Sahakian et al, 1995; Smith et al, 1991). In this study, these findings may explain the association between physiological states and altered AA metabolism, which was similar to those in previous reports (Chua et al, 2013; Kobayashi‐Otsugu et al, 2020; Wang et al, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…It has been reported organisms are more exposed to reactive oxygen species as they age and that reactive oxygen species cause the carboxylation of proteins, which reduces protein activity (Chakravarti & Chakravarti, 2007;Levine & Stadtman, 2001;Stadtman, 2006). In a previous study, the association between calpains and hypoxia-induced damage in retinal ganglion cells was reported in the human retinal explants (Kobayashi-Otsugu et al, 2020). In addition, it has been suggested that proteins can be oxidized by metal-catalyzed oxidation (Garland, 1990;Sell & Monnier, 2011;Stadtman, 2006).…”
Section: Introductionmentioning
confidence: 97%
“…One of the clinical hallmarks of AMD is drusen: protein and lipid aggregates that accumulate between the RPE and choroid. Notably, retinal explants from monkeys and humans under hypoxic stress (which models AMD in vitro) showed calpain activation due to accumulation of N-retinylidene-N-retinylethanolamine (A2E; a pyridinium bisretinoid), a principal component of drusen [120,121]. Importantly, the degenerating explants were rescued by application of a generic calpain inhibitor, SNJ-1945, suggesting that calpain activation is involved in AMD progression (Figure S5A in the supplemental information online) [122].…”
Section: Non-mendelian Ophthalmic Diseases Of Chronic Cellular Stressmentioning
confidence: 99%